The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1080/21597081.2016.1251379
|View full text |Cite
|
Sign up to set email alerts
|

Phagebiotics in treatment and prophylaxis of healthcare-associated infections

Abstract: We have developed a phagebiotic composition using 8 virulent bacteriophages (2 strains of each species) which are able to lyse Acinetobacter baumannii, Klebsiella pneumoniae, Pseudomonas aeruginosa and Staphylococcus aureus. The unique character of the developed composition is ensured by particular properties of each bacteriophage comprising the preparation, including their range of lytic activity toward specific bacterial pathogens, morphology of their plaques, cycle of their development, restriction profile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 4 publications
0
21
0
4
Order By: Relevance
“…Bacteriophage-coated tubes could be attended to inhibit bacterial adhesion, whereas direct application may be useful in reducing microbial bioburden. Aleshkin et al (2016) reported the intragastric administration of a phage cocktail in patients on mechanical ventilation, aiming for the treatment of acute infections caused by nosocomial pathogens. The authors demonstrated an important reduction in bacterial counts after phage therapy, indicating it as an alternative purpose to antibiotics to treat healthcare-associated infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteriophage-coated tubes could be attended to inhibit bacterial adhesion, whereas direct application may be useful in reducing microbial bioburden. Aleshkin et al (2016) reported the intragastric administration of a phage cocktail in patients on mechanical ventilation, aiming for the treatment of acute infections caused by nosocomial pathogens. The authors demonstrated an important reduction in bacterial counts after phage therapy, indicating it as an alternative purpose to antibiotics to treat healthcare-associated infections.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, new lytic bacteriophages able to control multidrug-resistant P. aeruginosa planktonic cells and associated-biofilm forms were described ( Yuan et al, 2019 ; Adnan et al, 2020 ). Although promising, there are few reports on bacteriophage applicability to control biofilms associated with endotracheal tubes ( Aleshkin et al, 2016 ). Thus, we consider it essential to clarify whether newly isolated bacteriophages can be applied in order to control P. aeruginosa biofilms on the surface of endotracheal tubes.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing rates of antimicrobial resistance, particularly against last-line drugs such as carbapenems, has led to a resurgence of interest in phage and monoclonal antibody therapies and vaccinations targeting K. pneumoniae (16)(17)(18)(19)(20)(21)(22)(23)(24)(25). There is particular interest in targeting the globally distributed MDR clones including CG258 (21)(22)(23)26).…”
Section: Application Of Kaptive Web To Track K and O Locus Diversity mentioning
confidence: 99%
“…In particular, the emergence and global dissemination of extended-spectrum beta-lactamase (ESBL) and carbapenemase producing (CP) clones is a major concern and has led to the recognition of K. pneumoniae as an urgent public health threat (14,15). With the lack of new antimicrobial therapies, there has been a resurgence of interest in alternative strategies such as phage therapy (16)(17)(18)(19), monoclonal antibody therapy (20)(21)(22)(23) and vaccination (24)(25)(26). Several therapeutic targets have been suggested, and the polysaccharide capsule (K antigen) and lipopolysaccharide (O antigen) are among the most frequent.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, two clinical problems have been associated with K. pneumoniae , the spread of multidrug-resistant (MDR) strains ( 3 ) and the emergence of hypervirulent (hypermucoviscous) variants belonging mainly to K-1, K-2, K-57, and some other capsule serotypes ( 4 ). Lytic bacteriophages are considered the most accessible and acceptable alternative (additive) to antibiotics against K. pneumoniae infections ( 5 7 ).…”
Section: Genome Announcementmentioning
confidence: 99%